Evaluation Of Awareness, Knowledge, Attitude, And Opinion On Environmental Sustainability Among Youths In Penang, Malaysia - Ariffin, Fatin Nabilla (2021)
The purpose of this research is to evaluate the level of awareness, knowledge, attitude, and opinion on environmental sustainability amongst youths in Penang. All data were analysed using the SPSS software. The findings found that the majority of youth learned about environmental sustainability issues through the website. A descriptive statistic in the form of mean was used to evaluate the level of awareness, knowledge, attitude, and opinion on environmental sustainability.